INFLUENCE OF IRON(IV) CLATROCHELATE ON IRON CONTENT IN SOME INTERNAL ORGANS OF PIGLETS - Derkach, I.; Dukhnitsky, V.; Derkach, S.; Lozovyі V.; Kostrub, V.; Losa, Yu.; Midyk, S.; Morozova, V.; Ushkalov, V.; Fritsky, I.; et al. (Scientific Progress & Innovations, 2021)
The reason for the development of iron deficiency anemia in newborn piglets is the delay of erythrocytopoiesis in the spleen and liver and insufficient restructuring of the hematopoietic capacity of the bone marrow. Extensive knowledge of the peculiarities of hematopoiesis in animals of this species allows to analyze the pathogenesis of anemia in piglets and to determine the role of various factors that cause this disease. The aim of our study was to determine iron content in the spleen and liver of piglets born to sows, which were injected intramuscularly with solutions of iron (IV) clatrochelate and cyanocobalamin. The article presents the results of our subsequent clinical trials to determine anti-anemic efficacy of iron in a new rare valence IV and in the form of clatrochelate. To achieve this goal, 2 groups of newborn piglets-analogues were formed during their keeping with nursng sows − control and experimental, 15 animals in each. The experiment lasted 30 days. The piglets in the experimental group were selected from sows given 10 ml of 10 % iron (IV) clatrochelate solution and cyanocobalamin solution twice intramuscularly during pregnancy. The piglets of the control group according to the traditional scheme of prevention of iron deficiency anemia on the second day of life were administered iron dextran preparation (at the rate of 200 mg of iron (III) per injection). The results of the studies indicate a sufficient intake of iron in piglets born to sows, which during pregnancy for 14 and 7 days before the expected farrowing were administered 10 % solution of iron (IV) clatrochelate and the solution of cyanocobalamin. A high content of ferrum microelement in the liver and spleen for 15 days was established, which exceeded the indicators at the use of the traditional iron dextran preparation uniferon to piglets. It can be argued that iron (IV) clatrochelate is characterized by high bioavailability, the ability to cross the placental barrier. The studies are scientifically and practically important, as they expand the knowledge of the pharmacokinetics and pharmacodynamics of high-valence iron (IV), and our proposed approach to the use of iron (IV) clatrochelate provides reliable and effective prevention of iron deficiency anemia in piglets.